Livelihood Asset Maps: Livelihood Assets Concerning The Echo-Agro-Tourism Community-Based Management of The Komunitas Cengkih Afo in Tongole Ternate-North Maluku - Mardiyani Sidayat; Mila Fatmawati (TECHNO: JURNAL PENELITIAN, 2021)
Humans need livelihood assets for their survival which particularly are related to the resources that are available in their environment and/or can be accessed to meet their needs. Livelihoods assets which are including capabilities, assets, and activities that carry out to support the fulfillment of basic life needs. The Department for International Development (DFID) identifies 5 categories of assets used for livelihoods which consist of human, natural, financial, physical,  and social capitals. The majority of people who live in Tongole Village work as farmers, and therefore by the presence of the echo-agro tourism activities, the livelihood assets of the community can increase and/or vary because there are other possible options to increase the economic income earned. The research is aiming to identify the use of livelihood assets by the farmer groups in Komunitas Cengkih Afo. The study has taken place in Tongole village,  where the Komunitas Cengkih afo is located. Collecting data is using a purposive sampling method, which refers only to the member of the Komunitas Cengkih Afo. Data on livelihood assets is taken base on the criteria set out according to the pentagon diagram which consists of human, natural, financial, physical, and social capitals. Livelihood assets are categorized in high, medium, and low categories from each respondent. The influence of livelihood assets was analyzed using a scoring method and presented in a pentagon diagram for each capital. Results showed that human, natural,  and social capital were the most utilized for all the members, while physical and financial capital was less utilized and/or at the moderate level.